The demography and characteristics of SARS-CoV-2 seropositive residents and staff of nursing homes for older adults in the Community of Madrid: the SeroSOS study. (4th May 2021) - Candel, Francisco Javier; Barreiro, Pablo; San Román, Jesús; del Mar Carretero, María; Sanz, Juan Carlos; Pérez-Abeledo, Marta; Ramos, Belén; Viñuela-Prieto, José Manuel; Canora, Jesús; Martínez-Peromingo, Francisco Javier; Barba, Raquel; Zapatero, Antonio; et al.
Abstract: Background: Nursing homes for older adults have concentrated large numbers of severe cases and deaths for coronavirus disease 2019 (COVID-19). Methods: Point seroprevalence study of nursing homes to describe the demography and characteristic of severe acute respiratory syndrome by coronavirus 2 (SARS-CoV-2) immunoglobulin G (IgG)-positive residents and staff. Results: Clinical information and blood samples were available for 9, 332 residents (mean age 86.7 ± 8.1 years, 76.4% women) and 10, 614 staff (mean age 45.6 ± 11.5, 86.2% women). Up to 84.4% of residents had frailty, 84.9% co-morbidity and 69.3% cognitive impairment; 65.2% of workers were health-aides. COVID-19 seroprevalence was 55.4% (95% confidence interval (CI), 54.4–56.4) for older adults and 31.5% (30.6–32.4) for staff. In multivariable analysis, frailty of residents was related with seropositivity (odds ratio (OR): 1.19, P = 0.02). In the case of staff, age > 50 years (2.10, P < 0.001), obesity (1.19, P = 0.01), being a health-aide (1.94, P < 0.001), working in a center with high seroprevalence in residents (3.49, P < 0.001) and contact with external cases of COVID-19 (1.52, P < 0.001) were factors associated with seropositivity. Past symptoms of COVID-19 were good predictors of seropositivity for residents (5.41, P < 0.001) and staff (2.52, P < 0.001). Conclusions: Level of dependency influences risk of COVID-19 among residents. Individual and work factors, contacts outside the nursing home are associated with COVID-19 exposure in staff members. It is key to strengthen control measures to prevent the introduction of COVID-19 into care facilities from the community.